Mental toughness the mindset behind sporting achievement - Sheard, Michael, 1968- (Routledge, 2012)
Mental toughness is one of the most common terms used in sport - by athletes, coaches, spectators and the media. However, it is also one of the least understood terms. This book examines the characteristics and development of mentally tough sport performers, and presents the cutting-edge research in this area. Within these chapters, the author proposes that mental toughness is a personality style and mindset, and presents a compelling case for its inclusion within the positive psychological paradigm.